2016
DOI: 10.1177/0969733015587777
|View full text |Cite
|
Sign up to set email alerts
|

Complaints filed against nursing professionals

Abstract: The findings can serve as input to guide nursing schools and boards of nursing in developing policies to raise awareness among nursing professionals, sensitizing them to the responsible provision of care in the light of bioethical and legal principles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 16 publications
(18 reference statements)
0
26
0
12
Order By: Relevance
“…The 17 studies were published in English between 2007 and 2016, and 12 were published between 2008 and 2011. We found that 14 studies were conducted in the USA, and there was one each from Australia (Chiarella & Adrian, ), Israel (Azuri, Haron, Riba, & Sar‐Lev, ) and Brazil (da Silva, Silva Candido, Duarte, & Santos, ; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 17 studies were published in English between 2007 and 2016, and 12 were published between 2008 and 2011. We found that 14 studies were conducted in the USA, and there was one each from Australia (Chiarella & Adrian, ), Israel (Azuri, Haron, Riba, & Sar‐Lev, ) and Brazil (da Silva, Silva Candido, Duarte, & Santos, ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Further three studies were reviews of legal cases related to disciplinary procedures, with no specific research method. The quantitative studies were conducted with statistical analysis methods (Azuri et al, ; Benton & Flynn, ; Hester, Green, Thomas, & Benton, ; Hudspeth, ; Kenward, ; Strong, ; Zhong, Kenward, Sheets, Doherty, & Gross, ; Zhong & Thomas, ), post hoc analysis (Evangelista & Sims‐Giddens, ), retrospective analytic desk research (da Silva et al, ), a longitudinal retrospective cohort study design (Hudson & Droppers, ) and comparative descriptive study design (Jones, Fitzpatrick, & Drake, ). The qualitative method used was content analysis (Azuri et al, ; Chiarella & Adrian, ; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, examples of bullying at work have been widely disseminated in the media and scientific literature and characterized as a type of toxic violence capable of degrading workers’ health (Wright & Khatri, ) and working conditions (Tsai, Han, Chen, & Chou, ). In Brazil, among interprofessional conflicts, bullying has been the primary reason for claims filed by nursing professionals to the Professional Council of Nursing (Schneider & Ramos, ; Silva, Camargo, Candido, Duarte, & Santos, ).…”
Section: Introductionmentioning
confidence: 99%